Pemanfaatan Media Pembelajaran Augmented Reality Bangun Ruang pada Mata Pelajaran Matematika di SMAN 01 Sungai Aur Pasaman Barat - Hasni, Ihdal; Zakir, Supratman (Indonesian Research Journal on Education, 2022)
The results of learning geometry for students, especially in the sub-material of building space, can be said to have very low learning outcomes, one of the factors is that they still use simple media as learning media in the classroom. For class XII learning media used are printed books / worksheets, and simple teaching aids such as cube and block frames as media used in learning. This makes a lot of students feel bored and havelittle interest in learning about the material of building space in mathematics because they only listen to the teacher speaking in front (lecture), but to understand the explanation of the material, build space, concentration and imagination of students as well as a conducive learning atmosphere. So we need a learning media that can help learning in order to create a conducive and active environment. The purpose ofthis study was to determine how much augmented reality development in mathematics subjects at SMAN 01 Sungai Aur Pasaman Barat. This study has two samples, namely class XII IPS 1 as an experimental class and class, XII IPS 2, as a control class. Simple random sampling is a method of taking samples from members ofthe population by using randomly regardless of the strata in the population. The research method used is a quasi-experimental design with a nonequivalent control group. The instrument used is a test instrument in the form of multiple choice questions. Results Based on the hypothesis by using the t-test on the test questions, thevalue of Sig. (2 tailed) is 0.018 and a significance development level of 0.05, it can be seen that the value of Sig. (2 tailed) > 0.05, so the hypothesis is H0 (there is no learning media). augmented reality building space at SMA N 01 Sungai Aur Pasaman Barat) was rejected, then H1 was accepted. With the acceptance of the H1hypothesis in testing the hypothesis, it can be said that there is a development of the effect of augmented reality in mathematics lessons.